P11.27.B Whole genome DNA methylation as predictive biomarker in CNS WHO grade 2 and 3 oligodendroglioma patients receiving early postoperative treatment. (5th September 2022) - Mair, M J; Leibetseder, A; Heller, G; Puhr, R; Tomasich, E; Hatziioannou, T; Woehrer, A; Widhalm, G; Dieckmann, K; Aichholzer, M; Weis, S; von Oertzen, T; et al.
Abstract: Background: Oligodendrogliomas are glial tumors with a relatively favorable survival prognosis of >10 years. While immediate postoperative treatment prolongs survival, long-term toxicities of adjuvant radio-chemotherapy remain a concern. Predictive biomarkers guiding postoperative treatment decisions are limited. Material and Methods: In this retrospective study, we included patients treated for a newly diagnosed oligodendroglioma (isocitrate dehydrogenase ( IDH )-mutated, 1p/19q-codeleted, CNS WHO grades 2 and 3) in 1992 - 2019 at the Medical University of Vienna or the Kepler University Hospital Linz (Austria). Early treatment was defined as radiotherapy, chemotherapy, or both within 6 months after resection, whereas benefit from early treatment was defined as progression-free survival (PFS) above the median in the overall cohort. DNA methylation analysis was performed using Illumina MethylationEPIC 850k microarrays. Results: Of all 201 eligible patients, sufficient tumor tissue for DNA methylation analysis was available in 46 patients. Of these, 25/46 (54.3%) were diagnosed with CNS WHO grade 2 and 21/46 (45.6%) with grade 3 oligodendroglioma. Median age at diagnosis was 41 years (range: 23-70). In total, 21/46 (45.6%) patients received early treatment, of whom 13/21 (61.9%) received radio-chemotherapy, 6/21 (28.6%) radiotherapy only and 2/21 (9.5%) chemotherapy only. Median PFS was 134.0 months (95%CI: 78.3 - not reached) in patients receiving early treatment versus 87.2 months (95%CI: 66.8 - 150) in patients who did not. In patients receiving early treatment, differences in DNA methylation profiles could be detected between patients who drew benefit from postoperative treatment (group 1) versus those who did not (group 2). Based on the top 1000 differentially methylated CpG sites between both groups, two clusters were detected which comprised either patients of group 1 or 2. Clustering was independent from gender, WHO grade, extent of resection, type of postoperative treatment, treating center, and O6-methylguanine-methyltransferease ( MGMT ) promoter methylation status. Gene set enrichment analysis of the top 1000 differentially methylated gene sites mapped to 694 genes showed differential methylation in genes involved in fibroblast growth receptor 1 (FGFR1) signaling, Wnt signaling, integrin signaling, and actin cytoskeleton regulation. Conversely, in patients not receiving early treatment, PFS did neither correlate with DNA methylation clustering nor with MGMT promoter methylation. Conclusion: In our cohort, whole genome DNA methylation was associated with PFS in patients who received early postoperative treatment, suggesting a predictive but not prognostic role. As the predictive value of MGMT promoter methylation is limited in oligodendroglioma, whole genome DNA methylation should be considered in future clinical trials.